The Influence of Family Support on Compliance with Antenatal Care (ANC) Visits among Pregnant Women - Nurfitria Andini, Rika; Sartika, Dona (Jurnal Kesehatan Cendikia Jenius, 2025)
Antenatal Care (ANC) visits are crucial for monitoring maternal and fetal health, managing pregnancy complications, and promoting healthy pregnancy outcomes. Family support plays a significant role in influencing ANC adherence. This study aimed to investigate the association between family support and ANC visit adherence among pregnant women in the Karang Tengah Health Center working area. A cross-sectional study was conducted with a population of 54 pregnant women. Data were analyzed using univariate and bivariate analysis with Spearman's Rank Correlation Test. The results of this statistical test obtained a significance value of 0.000 <0.05, which means Ha was accepted, indicating there is a relationship between the family support variable and the ANC visit compliance variable.Conclusion : Family support significantly influences compliance with ANC visits, improving the health of mothers and babies. It is recommended that families provide support, remind and accompany pregnant women during Antenatal Care (ANC) visits to improve the quality of health services.